M MODEL KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN ERA SOCIETY 5.0 : MODEL KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN ERA SOCIETY 5.0 - Riswandi; Rini, Riswanti; Surahman, Maman; Izzatika, Amrina; Ridha Utami, Nur (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2023)
The society 5.0 era is collaborative process of technology that becomes the power for every human being to carry out various activities. The aim of carrying out this service activity to provide understanding and knowledge as well as the readiness of school principals which must be designed to improve the quality of education in the society 5.0 era through transformational leadership. So that the specific target achieved is that participants can understand and apply the school principal's transformational leadership model to improve the quality of education in the era of society 5.0. The methods used to achieve the above goals and targets include lectures, brainstorming and discussions, role playing, and document analysis. The service results show that the average post-test percentage score for training participants is 76.21, the meaning was increased compared to the pre-test results for training participants is 72.06. Meanwhile, the average percentage increase in training participants' abilities from pre-test to post-test increased by 22%. In conclusion, teachers' understanding of the transformational leadership training model for school principals in the society 5.0 era was implemented well and optimally.